Year-round movements of white-chinned petrels from Marion Island, south-western Indian Ocean. Issue 3 (26th March 2018) - Rollinson, Dominic P.; Dilley, Ben J.; Davies, Delia; Ryan, Peter G.
Abstract: White-chinned petrels Procellaria aequinoctialis L. are the most frequently recorded procellariiform species in the bycatch of Southern Hemisphere longline fisheries. Our study investigated the year-round movements of ten adult white-chinned petrels (seven breeders, three non-breeders/suspected pre-breeders) from Marion Island tracked with global location sensor (GLS) loggers for three years. Additionally, 20 global positioning system (GPS) tracks were obtained from breeding white-chinned petrels during incubation ( n =9) and chick-rearing ( n =11). All GLS-tagged birds remained, year-round, in the area between southern Africa and Antarctica, not making any major east/west movements. Three core areas (50% kernels) were utilized: around the Prince Edward Islands (PEI; incubation and early chick-rearing), c . 1000 km west of PEI (pre-breeding and early incubation) and around South Africa (non-breeding birds). The only area where 50% utilization kernels overlapped with intensive longline fishing effort was off the Agulhas Bank (non-breeding season). Our results confirm the lack of foraging overlap between the two subspecies; nominate birds (South Georgia/south-western Indian Ocean) utilize separate areas to P. a. steadi (New Zealand/sub-Antarctic islands), and thus should be treated as separate management units. Knowledge of the year-round movements of a vagile species, such as the white-chinned petrel, is important for its continued conservation.